Diamond turned hierarchically textured surface for inducing water repellency: Analytical model and experimental investigations. (1st March 2021) - Prasad, K.K.; Roy, T.; Goud, M.M.; Karar, Vinod; Mishra, Vinod
Highlights: Force balance based mathematical model is developed to predict water contact angle on hierarchical textured surface. Diamond turning based single process multi-level texturing is done to fabricate the hierarchical structures The model is capable to predict the contact angle with 6.67% error. The designed and fabricated hierarchal is superhydrophobic with contact angle of 152° The proposed model, design and process are effective to generate the hierarchical structure in single process in cost effective way. Abstract: Functional surfaces have gained a lot of interest due to enhancement in water repellency for advanced engineering applications. In the present era, single and multi-level texturing is usually carried out on surfaces for inducing complete water repellency. The role of a hierarchical textured surface for enhancing the contact angle (CA), however, has not been extensively studied and understood. In the present work, the physical interpretation of water droplet activity on a hierarchical textured surface has been studied by the development of a mathematical model taking into account different forces responsible for inducing water repellency. Subsequently, hierarchical textured surface i.e., arrays of major pillars with rectangular sub-micron minor pillars over its top surface, were fabricated with high precision by using a diamond turn machining (DTM) process. The fabricated hierarchical textured surface was investigated based on the structural dimension and static CA. Also, the effects of variation of spacing between major pillars ( p ), the ratio of spacing between minor pillars to the minor pillar width ( k = p s w t ) and ratio of minor pillar to major pillar width ( v = w t w ) with CA were studied. The developed mathematical model was able to predict the water CA with dimensions similar to experimentally fabricated hierarchical textured surface with an error of 6.67%. The model is capable of designing and optimizing the hierarchical textured surface of various sizes, which enables their manufacturing in a cost-effective way. Graphical abstract: Image, graphical abstract